Which health care facilities do adult malawian antiretroviral therapy patients utilize during intercurrent illness? a cross sectional study - Masangalawe Caroline; Kandulu Akuzike; van Oosterhout Joep J (BMC, 2011)
Abstract Background Antiretroviral therapy (ART) clinic populations have expanded enormously in the successful Malawi ART scale-up programme. Overcrowding, long waiting times and living far away from the clinic may affect the extent to which patients use their ART clinic for intercurrent illnesses. Methods We interviewed patients of a large urban ART clinic in Blantyre, Malawi, during routine visits about the choice of health care facility during recent illness episodes. Results Out of 346 enrolled adults, mean age 39.8 (range 18-70) years, 54.3% female, 202 (58%) reported one or more illness in the past 6 months, during which 85 (42.1%; 95%-confidence interval: 36.9-47.3%) did not utilize their own clinic. Long distance to the clinic was the main subjective reason, while low education attainment, rural residence, perceived mild illness and dissatisfaction with the ART service were associated with not using their own clinic in multivariate analyses. Of all participants, 83.6% were satisfied with the service provided; only 6.1% were aware of the full service package of the ART clinic. Conclusions ART patients often seek health care outside their own clinic, which may have detrimental effects, and has consequences for ART counseling content and reporting of ART information in health passports.